2007
DOI: 10.1093/rheumatology/kel112
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous cyclophosphamide therapy for progressive interstitial pneumonia in patients with polymyositis/dermatomyositis

Abstract: In this open-label study, IVCYC improved symptoms, pulmonary function tests and HRCT findings in patients with PM/DM. Longitudinal controlled studies are required to further confirm the efficacy of IVCYC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(94 citation statements)
references
References 30 publications
3
82
0
9
Order By: Relevance
“…Takada et al reported that when comparing the results from 20 active cases of DM/PM-complicated IP, in which only additional immunosuppressive agents were added if corticosteroid alone did not result in a favorable response, with 14 additional cases in which immunosuppressive agents were combined with corticosteroids, the combination therapy led to a higher survival rate . Other clinical trials reported similar results (Yamasaki, 2007, Kotani, 2008. These reports indicate that early combined therapy is more effective than combining additional agents at a later time; as a result, this maximizes the effectiveness of the immunosuppressant.…”
Section: Treatment Of Ipsupporting
confidence: 52%
See 1 more Smart Citation
“…Takada et al reported that when comparing the results from 20 active cases of DM/PM-complicated IP, in which only additional immunosuppressive agents were added if corticosteroid alone did not result in a favorable response, with 14 additional cases in which immunosuppressive agents were combined with corticosteroids, the combination therapy led to a higher survival rate . Other clinical trials reported similar results (Yamasaki, 2007, Kotani, 2008. These reports indicate that early combined therapy is more effective than combining additional agents at a later time; as a result, this maximizes the effectiveness of the immunosuppressant.…”
Section: Treatment Of Ipsupporting
confidence: 52%
“…In the initial case reports, the effects of IV-CY were variable. Yamasaki et al administered IV-CY at doses of 300 to 800 mg/m 2 6 times every 4 weeks in addition to steroids to 17 patients with DM/PMcomplicated IP (Yamasaki, 2007). Dyspnea improved in 11 patients, %VC improved by 10% or more in 8 patients, and the chest CT score improved in 9 patients.…”
Section: Cyclophosphamidementioning
confidence: 99%
“…Several retrospective studies suggest its utility as second- [94] or third-line of treatment in chronic ILD (table 5) [93,95]. Its use as a first-line treatment or in refractory cases of rapidly progressing ILD needs to be further explored, with anecdotal responses reported in four patients in three studies [62,93,94].…”
Section: Tacrolimusmentioning
confidence: 99%
“…The combination of pulse-dosed CYC and corticosteroids in 17 refractory patients resulted in significantly improved dyspnea, vital capacities, and CT findings. The results of the trial in question suggest that CYC (IV) can be more effective during the early stages of the disease (18). In addition, early initiation of immunosuppressive agents (within 1 month of steroid therapy) is one of the predictive factor for better prognosis for the patients with DM complicated pnemomediastinum (15).…”
Section: Discussionmentioning
confidence: 99%